Peran Komunikasi Pembangunan dalam Pembangunan Infrastruktur di Kabupaten Konawe Kepulauan - Hado, Hado; Sjachrawy, La Ode Muhammad Ichwan; Taziruddin, Taziruddin; Mahdar, Mahdar; Kasim, Syaifudin Suhri (YASIN, 2025)
This study aims to analyze the implementation of development communication in village infrastructure development by the Lamongupa Village Government, Wawonii Tengah District, Konawe Kepulauan Regency. The main focus of this research is to understand how development communication is used to enhance community participation and support sustainable village development. The research method employed is a case study with a descriptive qualitative approach. Data were collected through observations, in-depth interviews, and document analysis conducted from November 2024 to January 2025. The analysis was carried out based on the concept of development communication, particularly the aspects of the right to communicate, democratization of communication, and the traditional knowledge system. The findings indicate that the Lamongupa Village Government has effectively implemented development communication in infrastructure development. The village government has provided opportunities for the community to participate in the planning and monitoring of development projects, including the improvement of a 580-meter village road, which has positively impacted accessibility and the local economy. Additionally, integrating cultural values and traditions into development communication has enhanced community acceptance of development policies. This study concludes that the application of inclusive development communication, grounded in local wisdom, can improve the effectiveness of infrastructure development and stimulate village economic growth. These findings highlight the importance of participatory communication in fostering sustainable village development.